ENHANCED ADAPTIVE FORECASTING MODEL AS A DECISION-SUPPORT TOOL IN TECHNOLOGY-ORIENTED FINANCIAL MARKETS (World Conference on Social Sciences, Law and Public Policy, 2026)
Forecasting stock performance in technology-oriented financial markets has become increasingly difficult due to the growing complexity of market behavior, rapid innovation cycles, and the constant influence of uncertainty. Unlike traditional industries, technology-oriented firms are often valued not only on the basis of their current financial indicators but also according to expectations regarding future growth, innovation potential, competitive advantage, and market expansion. This characteristic creates a forecasting environment in which conventional analytical models may provide only a limited understanding of future stock performance.
Keywords: interest-rate changes, inflationary pressures, geopolitical risks, regulatory developments, and technological transformations